The Pulsatile Gonadorelin Pump Induces Earlier Spermatogenesis Than Cyclical Gonadotropin Therapy in Congenital Hypogonadotropic Hypogonadism Men. Issue 1 (February 2019) - Zhang, Luyao; Cai, Ke; Wang, Yu; Ji, Wen; Cheng, Zhen; Chen, Guanming; Liao, Zhihong
The objective of this study was to compare the effect of pulsatile gonadorelin pump (PGP) and cyclical gonadotropin (human chorionic gonadotropin [HCG]/human menopausal gonadotropin [HMG]) therapy (CGT) on spermatogenesis in congenital hypogonadotropic hypogonadism (CHH) men. Twenty-eight azoospermic CHH males were included in this nonrandomized study. Ten received PGP and 18 received CGT. The primary endpoint was the earliest time spermatogenesis occurred during 24 months of treatment. Spermatogenesis time was significant earlier in the PGP group than the CGT group (median of 6 and 14 months, respectively, χ 2 = 6.711, p = .01). Spermatogenesis occurred in 90% of the PGP group and 83.3% of the CGT group and showed statistically insignificant difference in the superiority analysis and the no-inferior test. Contributing factors significant for spermatogenesis were previous HCG/or testosterone treatment and the peak serum luteinizing hormone level of triptorelin stimulation test at baseline. Although testis volume and penile length increased significantly from baseline, the differences between the two therapies were not significant. There was a tendency for high serum testosterone level, associated with more facial acne and breast tenderness in the CGT group. Skin allergic erythema scleroma was a common side effect of the PGP. In summary, PGP resulted in earlier spermatogenesis and more desirable testosterone levels than CGT.